KEMAMPUAN BERPIKIR KREATIF MATEMATIK SISWA MTs DITINJAU DARI KEMAMPUAN RESILIENSI MATEMATIK SISWA - Indiraningrum Pratiwi; Dwi Yulianti; Aflich Yusnita Fitrianna (IKIP Siliwangi, 2018)
This research aims to know where is the mistake of students on the tests of the ability of mathematical creative thinking in terms of the ability of mathematical resilience. The subject taken in this research that is grade VIII-A of MTs Fatahillah Cimahi consists of 26 students. This research used descriptive methods with qualitative and quantitative data analysis. Stages of the research done with 4 stages: filling the quisioner mathematical resilience, mathematical creative thinking ability test, data analysis and concluded. The results of this research were obtained: 1) students with high level of ability of mathematical resilience made a mistake at the indicator of original thinking skills (originality) and fluent thinking skills (fluency), 2) students with medium level of ability of mathematical resilience made a mistake at the indicator of detailed thinking skills (elaboration), 3) students with low level of ability of mathematical resilience made a mistake at the indicator of original thinking skills (originality), fluent thinking skills (fluency) and detailed thinking skills (elaboration).